2010
DOI: 10.1021/jo101762k
|View full text |Cite
|
Sign up to set email alerts
|

Folding and Unfolding Movements in a [2]Pseudorotaxane

Abstract: A new dibenzo[24]crown-8 derivative (1) was synthesized and functionalized with aromatic moieties such as naphthalene and coumarin units. These two fluorophores are known to form an effective FRET (Forster resonance energy transfer) pair, and this formed the basis for the design of this host crown ether derivative. Results of the steady-state and time-resolved fluorescence studies confirmed the resonance energy transfer between the donor naphthalene moiety and acceptor coumarin fragment, while NMR spectra and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 57 publications
4
51
0
Order By: Relevance
“…From the analysis of the binding constants shown in Table , several aspects can be highlighted: In the first place, the observed values are comparable with those reported in the literature for similar pseudorotaxanes . Besides, the complexes formed with OX‐4 have higher affinities than those with OX‐3 , which is consistent with the results obtained by the titrations using UV/Vis spectroscopy.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…From the analysis of the binding constants shown in Table , several aspects can be highlighted: In the first place, the observed values are comparable with those reported in the literature for similar pseudorotaxanes . Besides, the complexes formed with OX‐4 have higher affinities than those with OX‐3 , which is consistent with the results obtained by the titrations using UV/Vis spectroscopy.…”
Section: Resultssupporting
confidence: 88%
“…In this sense, we reasoned that they could be able to act as wheels and form pseudorotaxanes with dicationic axles derived from 1,2‐bis(benzimidazol‐2‐yl)ethane. Related complexes have been prepared previously using crown ethers, cyclodextrins, cucurbituril, and cyclophanes as wheels …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11] Thus, template methods have provided opportunities to develop different complicated threaded structures with many interesting properties. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] The first template-directed synthesis of an interlocked molecule comprised a rigid bidentate 1,10-phenanthrolinebased macrocycle and 1,10-phenanthroline derivatives templated with Cu I ions ("2+2" donor sets for tetrahedral complexes). [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] The first ...…”
Section: Introductionmentioning
confidence: 99%
“…[40] Ganguly et al demonstrated folding and unfolding movements in a [2]pseudorotaxane. [41] Schalley has found [4]pseudorotaxanes with remarkable self-sorting selectivities. [42] Philp developed a method of low temperature capture of pseudorotaxanes.…”
Section: Introductionmentioning
confidence: 99%